I10 Adherence to treatment and reduction in bmi sds associated with lower hba1c, 1 year after diagnosis of type 2 diabetes in youth. (12th March 2018) - Candler, TP; Mahmoud, O; Lynn, RM; Majbar, AA; Barrett, TG; Hamilton-Shield, JP
Abstract : Objective: To report outcomes from a national cohort of children and young people with type 2 diabetes (T2DM), 1 year post diagnosis Research design and methods 1 year follow up of a cohort of children (<17 years) with T2DM reported through the British Paediatric Surveillance Unit between April 2015 to April 2016. This established an overall UK incidence of 0.72 per 1 00 000 per year (2.92/100, 000 in Asians, 1.67/100, 000 Black/African/Caribbean/Black British) Results: Ninety-nine (93%) of the 106 notified cases had data available for one-year review. Of these, seven had been lost to follow up and one had the diagnosis revised. The mean age at follow up was 15.3 years. Of those with data, average BMI SDS was 2.72 with a mean increase of 0.14 SDS over a year (92% remained overweight or obese). Only 15% of cases achieved a reduction in body weight of 5% or more from baseline. Median HbA1c was 53 mmol/mol (range 31–130 mmol/mol) and 40% attained the UK national target of <48 mmol/mol. HbA1c was associated with BMI SDS change at 1 year (p=0.007) and clinician reported compliance and attendance concerns (p≤0.0001). In over half of cases, clinicians reported issues with compliance and attendance. Mean clinic attendance was 77%. Metformin was the most frequently used agent in management at baseline (77%) and follow up (87%). Microalbuminuria at 1 year was seen in 16.4% of cases compared to 4.2% at baseline. Conclusions: Good compliance and BMI reduction is associated with better outcomes, one year after diagnosis in early onset T2DM. It is concerning that the prevalence of microalbuminuria increases four-fold in this short time frame.